Communication Cultures, Organisational Culture, the Importance of Interculturality - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
At the level of the individual, the organisation and a society, the communication process, the prevailingcommunication style, the accepted and applied signals are significantly influenced by the culturalframework and roots of the given community. The aim of this chapter is to provide a brief overviewof this issue, in the course of which the role of cultures is highlighted at the social, organisationaland individual levels.The chapter also discusses about the definition of culture, the role on the field of negotiation styles,and the importance of organisational culture, especially when it comes to interactions between orwithin organisations.Keywords: organisational culture, communication culture, communication negotiation styles, concept of good governance, democratic techniques, interculturality